Degradation Diagnostics from the Subsurface of Lithium‐Ion Battery Electrodes. Issue 2 (30th August 2021) - Yao, Xuhui; Šamořil, Tomáš; Dluhoš, Jiří; Watts, John F.; Du, Zhijia; Song, Bohang; Silva, S. Ravi P.; Sui, Tan; Zhao, Yunlong
Abstract : Despite the long‐established rocking‐chair theory of lithium‐ion batteries (LIBs), developing novel characterization methodology with higher spatiotemporal resolution facilitates a better understanding of the solid electrolyte interphase studies to shape the reaction mechanisms. In this work, we develop a Xenon ion plasma focused ion beam (Xe + PFIB)‐based characterization technique to probe the cross‐sectional interface of both ternary cathode and graphite anode electrodes, with the focus on revealing the chemical composition and distribution underneath the electrode surface by in‐depth analysis of secondary ions. Particularly, the lithium fluoride is detected in the pristine cathode prior to contact with the electrolyte, reflecting that the electrode degradation is in the form of the loss of lithium inventory during electrode preparation. This degradation is related to the hydrolysis of the cathode material and the decomposition of the PVDF binder. Through the quantitative analysis of the transition‐metal degradation products, manganese is found to be the dominant element in the newly formed inactive fluoride deposition on the cathode, while no transition metal signal can be found inside the anode electrode. These insights at high resolution implemented via a PFIB‐based characterization technique not only enrich the understanding of the degradation mechanism in the LIBs but also identify and enable a high‐sensitivity methodology to obtain the chemical survey at the subsurface, which will help remove the capacity‐fade observed in most LIBs. Abstract : A Time‐of‐Flight secondary ion mass spectrometry (ToF‐SIMS) attached Xenon ion plasma focused ion beam and scanning electron microscope (Xe + PFIB‐SEM) characterization technique has been developed to characterize the cross‐sectional interface of lithium‐ion battery electrodes, featuring high‐sensitivity and high‐precision observations of chemical information by in‐depth analysis of secondary ions to reveal the degradation of electrodes.